The Effectiveness of Scaevola tacada Extract (Gaertn roxb) on the Level of Cytokine IL-10 of Strain Sprague dawly (Female Laboratory Rats) Induced by the Staphylococcus Aureus Bactera - Andi Sitti Umrah (Universitas Muhammadiyah Surabaya, 2018)
Background: Staphylococcus aureus is a sort of bacteria causing mastitis on women, generally found after delivery and during breastfeeding. These bacteria stimulate the immune system to respond, during which Sitikon is released. IL-10 is an anti-inflmation that impedes cell damage on the body, so it is required to do a complementary therapy stemming from the extract of Scaevola Taccada extract (Gaertn Roxb), generally known as sea lettuce. This study aimed to examine the effectiveness of Scaevola Taccada extract (Gaertn Roxb) on the level of Sitokin Il-10 of Strain Strain Sprague Dawly (Female Laboratory Rat) induced by the Staphylococcus Aureus Bacteria.Methods: This true experimental study employing pre- and post-test control design used 18 Sprangue Dawley, laboratory rats, that weighed between 200-250g, and that were divided into three groups, each of which comprised of six rats. The negative control group, positive control group and expiremental group were respectively given 1ml of aqua pro injection/250grBB rats, 9.6mg/ml of antibiotic amoxicillin/250gramBB rats, and 9.6mg of antibiotic amoxicillin/250grBB + 400mg/ml of Scaevola Taccada extract (Gaertn Roxb)/kgBB rats for five days. The sea lettuce plants were taken from the district of Pinrang, South Sulawesi. All groups were induced by staphylococcus aureus 0.2 ml x108 ml/CFU. The level of IL-10 was investigated using R&D method system ELISA Rat, in which the data were analyzed using ANOVA + post hoc test formula with the significant value ρ ≤ 0.05 and CI 95%.Results: The empirical evidence showed that there was no a significant different of Sitokin IL-10 level, either before or after the induction of the bacteria staphylococcus aureus for the length of ± 24 hours of all groups (ρ > 0.05). It was also found that there was a different level of IL-10 after the treatment between all of the groups given the value ρ < 0.05. The increase of IL-10 level was higher in the experimental group (mean ± 72,8 pg/ml) compared to the positive control group (mean ± 41, pg/ml).Conclusions: This research concluded that giving the extract of Scaevola taccada (Gaertn)Roxb) was effective in the boost of sitokin IL-10 level as an anti inflammation that plays central role in the stimulation of immune responses and the prevention of lichen imunopatologia development. The extract of sea lettuce (Scaevola taccada (Gaertn)Roxb)) can be given as a complementary therapy.